Medical Imaging and Augmented Reality 7th International Conference, MIAR 2016, Bern, Switzerland, August 24-26, 2016, Proceedings - Zheng, Guoyan; Liao, Hongen; Jannin, Pierre; Cattin, Philippe; Lee, Su-Lin (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2016)
The 6th International Conference on Medical Imaging and Augmented Reality, MIAR 2016, was held in Bern, Switzerland during August 2016. The aim of MIAR is to bring together researchers in computer vision, graphics, robotics, and medical imaging to present the state-of-the-art developments in this ever-growing research area in topics such as: Medical Image Formation, Analysis and Interpretation Augmented Reality, Visualization and Simulation Computer Assisted Interventional and Robotics, Surgical Planning Systematic Extra- and Intra-corporeal Imaging Modalities General Biological and Neuroscience Image Computing.